KEUNTUNGAN USAHA NASI KUNING KIOS YU CHIA DI KELURAHAN BANJER KECAMATAN TIKALA KOTA MANADO - Novan ., Winokan; Vicky Richard B. Moniaga; Agnes Estephina Loho (Sam Ratulangi University, 2020)
This study aims to determine how much profit from Yu Chia Kiosk yellow rice business in Banjer Village, Tikala District, Manado City. This research was conducted during November 2019. The data used in this study are primary data obtained from interviews with business owners. Data collection methods used in this study were direct interviews with yellow rice business owners in the form of cost, price, and quantity of yellow rice products. Data analysis used in this study was descriptive data analysis and presented in the form of tables and profit analysis. The results of the study showed that the profit gained from this business was Rp. 628,915 per day. *eprm*